Moderasi Khawarij Ibadiyah - Rofiq, Ahmad Choirul (IAIN Ponorogo, 2012)
Generally many historians depict Kharijite sect with negative image as a group that has an extreme religious ideas and nonconformist political attitudes. Furthermore Kharijite sect was regarded as an extremist faction and radical terrorist who prefers violence against any goverment that has deviated from Islamic doctrine according to Kharijite perspective. Similar to many religious sects, Kharijite sect also separated into many factions. This separation is usually caused by difference views that frequently arouse a dispute and conflict among them. In addition, they occasionally consider another faction as an unbeliever and infidel group. Because of this schism, the Kharijite sect became very weak so that can be destroyed easily. One of the Kharijite factions is Ibadite faction that is assessed by scholars as the closest faction to Sunnite sect because the Ibadites have moderate views so that can survive and exist until now whereas almost Kharijite factions tend to have extreme views and perform violent actions to achieve their aims. The successful indoctrination and thorough strategy might cause this moderation attitude.